When things go wrong: protecting patients and supporting doctors. Issue 9 (September 2018) - Taylor, Irving
Abstract: A healthcare system should ensure that surgical errors are kept to a minimum, and if possible are avoided altogether. Unfortunately, errors do occur however carefully one tries to avoid them. Once recognized an error must be rectified as soon as possible. An appropriate apology to the patient or their relative is an absolute requirement. In this article I review the processes available to deal with errors both locally and through the regulatory authorities if considered necessary. I look at how lapses, both clinical and non-clinical, are handled locally and by the appropriate regulatory body. I also discuss how allegations relating to fitness to practise are investigated. Whilst the over-riding responsibility of all these structures is to protect patients, as mentioned it is necessary also to support doctors and to learn the lessons on how and why the errors have occurred. The maintenance of professionalism is essential. As well as supporting and protecting the patient, support for the surgeon in the workplace is a necessary requirement.